2017
DOI: 10.1038/cdd.2017.70
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Twist1-mediated invasion by Chk2 promotes premature senescence in p53-defective cancer cells

Abstract: Twist1, a basic helix-loop-helix transcription factor is implicated as a key mediator of epithelial-mesenchymal transition (EMT) and metastatic dissemination in p53-deficient cancer cells. On the other hand, checkpoint kinase 2 (Chk2), a major cell cycle regulatory protein provides a barrier to tumorigenesis due to DNA damage response by preserving genomic stability of the cells. Here we demonstrate that Chk2 induction proficiently abrogates invasion, cell scattering and invadopodia formation ability of p53-mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 40 publications
2
27
0
Order By: Relevance
“…Then, by western blot screening and subsequent confirmatory assays, we identified that p38 is a novel target gene of DPYD in HCC, and could regulate NF-κB/Snail1 signaling in DPYD-induced EMT (Figs. 7 and 8 ) 23 , which is in concordance with the effects in other cell lines as previously reported 24 26 . However, the other EMT markers, such as vimentin, MMP2, and Twist1, were not observed to be involved in the DPYD-mediated EMT in HCC.…”
Section: Discussionsupporting
confidence: 92%
“…Then, by western blot screening and subsequent confirmatory assays, we identified that p38 is a novel target gene of DPYD in HCC, and could regulate NF-κB/Snail1 signaling in DPYD-induced EMT (Figs. 7 and 8 ) 23 , which is in concordance with the effects in other cell lines as previously reported 24 26 . However, the other EMT markers, such as vimentin, MMP2, and Twist1, were not observed to be involved in the DPYD-mediated EMT in HCC.…”
Section: Discussionsupporting
confidence: 92%
“…Various therapies aim to restore the capacity to senesce in cancer cells. As an example, overexpression of Chk2 was found to help restore senescence in some p53-deficient cancer cells [ 18 , 45 ]. In line with this finding, inhibition of ATR/ATM or Chk1/Chk2 was found to delay the onset of replicative senescence [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…The downregulation of p53 (a vital tumor suppressor) is a primary causative factor for colon cancer. The mutation or functional loss of p53 have been identified in >50% of human tumor cells (43,44). Stress can activate the p35 signal, such as p38 MAPK (21).…”
Section: Discussionmentioning
confidence: 99%